Changing the Game - Christie, Graham; Vullings, Michael (Ascent Audio, 2021)
As digital technologies and consumer expectations continue to disrupt almost every industry sector, companies are placing greater emphasis on developing and implementing transformation programs. Changing the Game offers the practical knowledge required to create a dramatic step-change in company performance. Designed for executives and managers responsible for a transformation in any type of company and situation, this comprehensive real-world playbook covers the change process from start to finish-from assessing the situation and determining strategic priorities, to developing a roadmap, establishing the governance structure, managing initiative delivery, and evaluating the impact of the transformation. Adopting a robust and pragmatic approach to every stage of business transformation, this authoritative volume explains where to start, identifies key areas of focus, and describes the strategies, decisions, and actions necessary for achieving results. Throughout the book, case studies of leading organizations highlight essential tools and approaches, examine key challenges, and evaluate their impact. A wealth of practical tools help listeners build a foundation for change in their organization, define a clear path forward, mobilize teams, assign responsibilities, execute initiatives, track progress, sustain momentum, and more.